Artificial intelligence in public service and governance in Nigeria - Nwosu, Chibuzo Charles; Obalum, Dike Chijioke; Ananti, Mathias Ozoemena (Goodwood Publishing, 2024)
Purpose: This study explores the current state of artificial intelligence implementation in Nigeria’s public service and the potential benefits, challenges, and strategic steps needed to harness AI for improved governance and service delivery. Methods: The research design was qualitative. The data were collected using secondary data collection, in which a thorough literature review of academic articles, books, and reports related to AI was consulted. This study applied a thematic research approach to clarify the underlying issues, beliefs, and experiences related to artificial intelligence in governance and public services. The study was also anchored to content analysis. Results: The findings revealed that AI application in Nigeria’s public service is still in its early stages, with promising developments in areas such as e-governance, healthcare, banking sector, real estate business, and law enforcement/security outfits. There is a need for the government in Nigeria to invest significantly in infrastructural advancement and human capital development, which in turn will close the skill gaps, infrastructural deficits, and lapses that crop up from the unawareness of Artificial Intelligence in the technological advancement of Nigeria. Limitations: This study examined the current state of AI in Nigeria's public services and governance by identifying the key barriers that affect the adoption and implementation of AI. The study made progressive recommendations that integrated the application of artificial intelligence in public services and governance in Nigeria. Contributions: This study provides a comprehensive understanding of how AI can be adopted in Nigeria’s unique environment. Findings: This study did not receive any funding from any agency or organization.